A Study to Assess the Effect of Video-Assisted Teaching on Knowledge and Attitude Regarding Prevention of Head Injury among Young Adults in Selected Colleges of Guwahati, Assam - Das, Barasa (Indian Journal of Nursing Sciences, 2024)
Introduction: The young adults need to be aware of head injury and its preventive aspects. They need to understand the causes of head injury, risk factors, and its application of preventive measures. It is utterly important and urgent to make aware and motivate young adults to practice preventive measures of head injury. Aim: This study aims to assess the effect of video-assisted teaching on knowledge and attitude regarding prevention of head injuries among young adults. Materials and Methods: The study sample consists of 50 young adults from different colleges of Guwahati, Assam. The methods and materials used were self-administered questionnaires and 4-point Likert Scale. Results: The study revealed, before the intervention, 58% had inadequate knowledge and none of them had adequate knowledge. After the intervention, 70% of them had adequate knowledge and none of them had inadequate knowledge. Before the intervention, 21% had inadequate attitude and none of them had adequate attitude. After the intervention, 32% had adequate attitude and 4% of them had inadequate attitude. The study revealed that there is a significant relationship between knowledge and attitude and found association between pre-test knowledge score of the young adults on prevention of head injury with their gender as well as between the pre-test attitude score on prevention of head injury with their age and educational qualification. Conclusion: The study revealed that the video-assisted teaching was effective and it improved knowledge and attitude of young adults on prevention of head injury.